Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fcell.2021.702462
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Demethylase KDM6 Enhances Early Neuroectoderm Commitment of Human PSCs

Abstract: Epigenetic modifications play a crucial role in neurogenesis, learning, and memory, but the study of their role in early neuroectoderm commitment from pluripotent inner cell mass is relatively lacking. Here we utilized the system of directed neuroectoderm differentiation from human embryonic stem cells and identified that KDM6B, an enzyme responsible to erase H3K27me3, was the most upregulated enzyme of histone methylation during neuroectoderm differentiation by transcriptome analysis. We then constructed KDM6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…KDM6B, an enzyme that modifies histones, plays an essential role in early neurogenesis. Inhibition of its expression can promote neuroectodermal differentiation of human pluripotent stem cells [ 19 ]. In this study, we aim to analyze the biological role and mechanism of KDM6B in repairing neural tissue using SCAPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KDM6B, an enzyme that modifies histones, plays an essential role in early neurogenesis. Inhibition of its expression can promote neuroectodermal differentiation of human pluripotent stem cells [ 19 ]. In this study, we aim to analyze the biological role and mechanism of KDM6B in repairing neural tissue using SCAPs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, KDM6B is involved in regulating the development of medial, lateral, and preganglionic motor columns [ 18 ]. In the directed neuroectodermal differentiation system of human embryonic stem cells, it has been observed that the knockout of KDM6B leads to a higher efficiency of neuroectodermal induction in human pluripotent stem cells [ 19 ]. The origin of cells used in neuro-regenerative medicine is a matter of concern, with embryonic stem cells and neural stem cells being the ideal sources as they can serve as seed cells while shaping the neural regeneration microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, KDM6A mutations are associated with increased "stemness" in cancer and Kdm6a KO impairs mesoderm development in vivo largely through histone demethylase-independent mechanisms [20]. However, recent studies of Kdm6a KO models indicate that depletion of the enzyme does not block differentiation, and may even facilitate differentiation into neuroectoderm lineages [35,36]. Indeed, we only observed effects on germ layer marker genes after XCI has occurred and our KDM6A chromatin binding analyses suggest a direct effect of KDM6A on Xist expression during early XCI rather than an effect on differentiation itself.…”
Section: Discussionmentioning
confidence: 99%
“…Meng et al. discovered that Inhibition of KDM6 (histone H3K27me3 demethylase) can improve neuroectoderm induction from both ES cells and iPS cells ( Meng et al., 2021 ). In addition, deletion of KMT2D (encoding histone H3K4 methyltransferase) may cause precocious iPSC-derived neuronal maturation due to transcriptional suppression of metabolic genes and proliferation defects ( Carosso et al., 2019 ).…”
Section: Histone Modifications In Neurodifferentiation Of Induced Pluripotent Stem (Ips) Cellsmentioning
confidence: 99%